2018
DOI: 10.1021/acs.jpcc.7b12241
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling of Univalent Cation Exchange in Zeolite N

Abstract: Molecular dynamics simulations are used to investigate the hydration energy and ion-exchange properties of a synthetic zeolite, zeolite N with composition |K10(H2O)8Cl2|[Al12Si12O40]. The exchange of K+ ions with univalent ions such as NH4 +, Na+, Rb+, and Cs+ is investigated under a range of simulation conditions using a three-dimensional membrane in an electrolyte box containing explicit water molecules. Hydration energy calculations indicate that zeolite N prefers eight water molecules per cage, which is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 38 publications
(84 reference statements)
4
12
2
Order By: Relevance
“…Moreover, Zwingmann et al [7] showed that ammonium exchanged zeolite N is an ideal slow release fertiliser for sandy soils due to the high retention capacity of zeolite N for NH 4 + ions. Our computational results from previous [10] and this study for NH 4 + retention are consistent with these experimental results. This study shows that NH 4 + has the highest retention between all exchanging systems in zeolite N membranes along both crystallographic directions.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Moreover, Zwingmann et al [7] showed that ammonium exchanged zeolite N is an ideal slow release fertiliser for sandy soils due to the high retention capacity of zeolite N for NH 4 + ions. Our computational results from previous [10] and this study for NH 4 + retention are consistent with these experimental results. This study shows that NH 4 + has the highest retention between all exchanging systems in zeolite N membranes along both crystallographic directions.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous simulation outcomes [10] show similar conditions regarding the total number of cations retained in the membrane. These results suggest that the zeolite N structure prefers to hold no more K or other cations than an approximately equilibrium value.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations